Locked down and online women, sexuality, and the pandemic - Alcantara, Diana Faith F. (2022)
The COVID-19 pandemic took over the internet. With the series of lockdowns and stay-at-home policing, the majority of people?s social interactions are happening online. Omegle is one of the websites that surge in popularity during the extended periods of social isolation brought by this global health crises. However, Omegle is a very controversial site where encounters of nudity on camera were experienced by most users, especially women. Female users were vulnerable subjects of unwanted nudes from male strangers and victims of online sexual harassment. Using qualitative approach, this study presents identities. Of women in Omegle, their motivation and experiences using the site before and during the pandemic, and other implications of womanhood. Data sources for this study include fieldwork observations and key-informant interviews. The study focuses only on the heterosexist norm of interaction in Omegle which concentrates mainly on the narratives of cis-heterosexual women. The results of the study demonstrate various identities of the female users in Omegle. Before the pandemic, most women were unaware of the sexual nature of the site and were motivated primarily by curiosity. During the pandemic, women already had prior knowledge about the site and used Omegle to seek online interaction regardless of its controversies. Negative experiences of unwanted penis encounters were prominent. To gain some control over these negative circumstances in Omegle, women displayed different forms of resistance-showing emotions, verbally reacting, taunting and fooling indecent men, and judging men?s penis sizes. The study recognizes insufficiencies in drawing aggregate representatives of female users of Omegle. Nevertheless, this remains significant for creating a safe online space for women.